-2(3s-5)-10=-3(5s+3)-5

Simple and best practice solution for -2(3s-5)-10=-3(5s+3)-5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(3s-5)-10=-3(5s+3)-5 equation:


Simplifying
-2(3s + -5) + -10 = -3(5s + 3) + -5

Reorder the terms:
-2(-5 + 3s) + -10 = -3(5s + 3) + -5
(-5 * -2 + 3s * -2) + -10 = -3(5s + 3) + -5
(10 + -6s) + -10 = -3(5s + 3) + -5

Reorder the terms:
10 + -10 + -6s = -3(5s + 3) + -5

Combine like terms: 10 + -10 = 0
0 + -6s = -3(5s + 3) + -5
-6s = -3(5s + 3) + -5

Reorder the terms:
-6s = -3(3 + 5s) + -5
-6s = (3 * -3 + 5s * -3) + -5
-6s = (-9 + -15s) + -5

Reorder the terms:
-6s = -9 + -5 + -15s

Combine like terms: -9 + -5 = -14
-6s = -14 + -15s

Solving
-6s = -14 + -15s

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '15s' to each side of the equation.
-6s + 15s = -14 + -15s + 15s

Combine like terms: -6s + 15s = 9s
9s = -14 + -15s + 15s

Combine like terms: -15s + 15s = 0
9s = -14 + 0
9s = -14

Divide each side by '9'.
s = -1.555555556

Simplifying
s = -1.555555556

See similar equations:

| .24(18)+0.04x=0.08(24+x) | | 2r^2-6r/r-3 | | 5w^2+7w=6 | | 2p+7=5-(11p+6) | | 5/4+2y=4y-1/4 | | .3(6)+.05x=.15(30+x) | | lx-4l=3 | | 6x^2=12x-16/3 | | 6(v+1)-2v=2(2v+2)-11 | | 7+13y-5=9y+18-4y | | 11/6+1/5t=4 | | 3x+2x+2=9 | | 7822-3008= | | x^3-12x+35=0 | | 5k+24=k-8 | | 3x+14x+6=10 | | x-5=70 | | 9n^2+6n-3=3 | | 10x+13y=4620 | | 7/5+1/4t=5 | | 5x^2-5x-910=0 | | 4+4i/6-3i | | 7b-8=5b+4 | | -10x-19=-209 | | s=2X^2-10X+50 | | 6s^2-11s=35 | | UC=2X^2-10X+50 | | 6s^2+11s=35 | | 3y-8=6y+28 | | 168.08=2.82w+14.9 | | 6(4y-1)=18y | | 7x-1+6x+2=2x+4 |

Equations solver categories